Analysis of molecular resistance and associated risk factors in tuberculosis - Zhenzhen Wang; Tengfei Guo; Liyang Xu; Jinwei Liu; Long Li; Junrong Jin; Qing Zhang; Tao Jiang; Zhanqin Zhao; Yun Xue (BMC Infectious Diseases)
Abstract Background Local surveillance of molecular resistance to first-line anti-tuberculosis (TB) drugs and fluoroquinolones (FQs) was initiated in 2019, but existing reports remain limited, hindering effective TB prevention and control efforts. This study aims to investigate molecular resistance to first-line anti-TB drugs and FQs, assess risk factors for FQs resistance, and provide insights into the spread of drug-resistant tuberculosis (DR-TB) to inform more effective control and treatment strategies. Methods Sputum samples from 25,150 non-duplicate patients attending 10 designated TB medical institutions across Luoyang City and all county and township areas under its jurisdiction from January 2019 to December 2023 were analyzed via fluorescence real-time PCR to detect Mycobacterium tuberculosis complex (MTBC)-positive strains. Multicolor melting curve analysis (MMCA) was performed on 4,131 non-repetitive MTBC strains to assess their molecular resistance to first-line anti-TB drugs and FQs. Risk factors for FQs resistance and the impact of first-line anti-TB drug resistance on FQs resistance were also assessed. Results Between 2019 and 2023, 4,131 MTBC strains were collected. Resistance to first-line anti-TB drugs was higher in males, retreated patients, individuals younger than 61 years, and those from the main urban area, compared to females, newly diagnosed patients, individuals over 60 years, and residents of county and township areas (59.1% vs. 46.0%, p < 0.001; 85.6% vs. 52.0%, p < 0.001; 60.2% vs. 47.2%, p < 0.001; 47.1% vs. 69.4%, p < 0.001). The overall FQs resistance rate was 7.9% (327 cases). After adjusting for the interaction with first-line anti-TB drugs, the resistance rates to FQs were significantly higher in patients with isoniazid resistance (INH-R), rifampin resistance (RFP-R), and ethambutol resistance (EMB-R), with odds ratios of 2.61 (95% CI 1.77, 3.84, p = 0.002), 4.64 (95% CI 3.13, 6.89, p < 0.001), and 2.86 (95% CI 2.01, 4.07, p < 0.001), respectively, compared to those without resistance. Conclusions Resistance to first-line anti-TB drugs remains high, underscoring the critical role of FQs in TB management. However, the elevated FQs resistance limits their effectiveness against drug-resistant TB. Strengthening DR-TB surveillance and implementing timely, targeted interventions are essential for controlling the spread of DR-TB and achieving the goals of the "End TB Strategy."